In situ reductive dissolution to remove Iodine-129 from aquifer sediments. (May 2020) - Szecsody, Jim E.; Emerson, Hilary P.; Pearce, Carolyn I.; Gartman, Brandy N.; Resch, C. Tom; Di Pietro, Silvina A.
Abstract: The use of an aqueous reductant (Na-dithionite) with pH buffer (K-carbonate, pH 12) was evaluated in this laboratory study as a potential remedial approach for removing Fe oxide associated iodine and enhancing pump-and-treat extraction from iodine-contaminated sediments in the unconfined aquifer in the 200 West Area of the Hanford Site. X-ray fluorescence data of untreated sediment indicated that iodine was largely associated with Fe (i.e., potentially incorporated into Fe oxides), but XANES data was inconclusive as to valence state. During groundwater leaching, aqueous and adsorbed iodine was quickly released, then additional iodine was slowly released potentially from slow dissolution of one or more surface phases. The Na-dithionite treatment removed greater iodine mass (2.9x) at a faster rate (1–4 orders of magnitude) compared to leaching with groundwater alone. Iron extractions for untreated and treated sediments showed a decrease in Fe(III)-oxides, which likely released iodine to aqueous solution. Solid phase inorganic carbon and aqueous Ca and Mg analysis further confirmed that significant calcite dissolution did not occur in these experiments meaning these phases did not release significant iodine. Although it was expected that, after treatment, 127 I concentrations would eventually be lower than untreated sediments, continued, elevated iodine concentrations for treated samples over 750 h were observed for leaching experiments. Stop flow events during 1-D column leaching suggested that some iodide precipitated within the first few pore volumes. Further, batch extraction experiments compared iodine-129/127 removal and showed that iodine-129 was more readily removed than iodine-127 suggesting that the two are present in different phases due to their different origins. Although significantly greater iodine is removed with treatment, the long-term leaching needs to be investigated further as it may limit dithionite treatment at the field scale. Graphical abstract: Image 1 Highlights: 127 I and 129 I in sediments quickly desorbs and also significant mass slowly leaches from solids. 127 I and 129 I in Fe-oxides was mobilized by reductive dissolution using Na dithionite. The Na-dithionite removed greater iodine mass and at a significantly higher rate. Continued long-term release of iodine from treated sediments is a challenge.